Acquisition risk factors of the SCCmec ix-methicillin-resistant staphylococcus aureus in swine production personnel in Chiang Mai and Lamphun Provinces, Thailand - Peerapat Rongsanam (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Methicillin-resistant Staphylococcus aureus (MRSA) harboring the type-IX staphylococcal cassette chromosome mec (SCCmec) has been found in pigs and humans in Northern Thailand. However, knowledge of the prevalence and acquisition risk factors of this MRSA strain among swine production personnel (SPP) are needed. The nasal swab samples and data were collected from 202 voluntary SPP and 31 swine farms in Chiang Mai and Lamphun Provinces, Thailand in 2017. MRSA were screened and identified using mannitol salt agar, biochemical and antimicrobial susceptibility testing, multiplex PCR, and the SCCmec typing. The prevalence of MRSA was 7.9% (16/202) and 19.3% (6/31) among SPP and swine farms. All isolates were multidrug-resistant, and 55 of 59 isolates (93%) contained the type-IX SCCmec element. Data analysis indicated that education, working time, contact frequency, working solely with swine production, and personal hygiene were significantly related to MRSA acquisition (p < 0.05). The multivariate analysis revealed that pig farming experience, working days, and showering were good predictors for MRSA carriage among SPP (area under the curve (AUC) = 0.84). The biosecurity protocols and tetracycline use were significantly associated with MRSA detection in pig farms (p < 0.05). Hence, the active surveillance of MRSA and further development of local/national intervention for MRSA control are essential.